Pengembangan Paduan Al-Si Hipereutektik yang akan Diterapkan untuk Komponen Otomotip - Akhmad Saufan (Jurnal Teknik Mesin, 2012)
This research will develop the hypereutectic Al-Si alloy that will be used to make automotive parts. The progress of this study is to make three alloy compositions; Al-30Si, Al-35Si and Al-40Si. The making process of the alloys by melting and alloying which are then poured into steel tube mold at different casting temperatures but the same superheat 100oC. The cast products are then metallographic tested and hardness tested. The microstructure of those three cast alloy products is cast structure consisting of much elongated large proeutectic silicon phase, the lamellar eutectic phase, chill structure, and cast defects consisting of shrinkage and porosity. The Brinell Hardness Number of the three cast products show that hardness of the Al-Si alloy will increase by increasing silicon content.